FAKTOR-FAKTOR YANG MEMPENGARUHI INSOMNIA PADA LANSIA DI PANTI TRISNA WERDHA “ILOMATA” KOTA GORONTALO TAHUN 2013 - Syamsul Anwar; Rona Febriyona (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Insomnia in the old people needs more attention. This problem wiil influences their physicsability, cognitive ability and their guality of live, The aim of this research to find out the factors of insomnia influences to the old people. This research using analitycal survey with cross sectional design. The sample in this research are the old people who lives in panti tresna werdha “ILOMATA” Gorontalo city. The data collecting by guestionary and chi square as data analyzes. This research found : (1) has influences the illness response to insomnia p=0,002, it means value more less from value of p=0,005. (2). This research has influences between environment of people toward to insomnia with result of p=0,006 it means more less from p value =0,005 (3). Has influences between insomnia and desperation toward ages and life style result of p=0,004 it means more less from p=0,005 (4) there is has not influences of ages and life style to insomnia with p result more than p value =0,005. The conclusion of this research is the illness response, environment, and desperation of old people has significant influences toward insomnia, in other hand ages and life style has not significant influences toward insomnia. The researcher has several suggestion to the keeper of that panti tresna werdha for give more attention to the old people who lives there, and for the department who has responsibility of this case for giving the seminars about the quality live of the old people.